Paraneoplastic polyarthritis in association with metastatic neuroendocrince tumour of the adrenal gland - Shetty, Sahana (Australasian Medical Journal, 2014)
Paraneoplastic polyarthritis is a rare manifestation described in association with various solid tumours. We describe the clinical presentation, diagnostic evaluation, differential diagnosis, and management of a 28-year-old woman who presented with fever, weight loss, and symmetrical polyarthritis, subsequently diagnosed to have a metastatic neuroendocrine tumour of the adrenal gland with paraneoplastic polyarthritis. Paraneoplastic polyarthritis must be considered in polyarthritis unexplained by common aetiologies. The unusual presentation of this case, alerts us about the atypical presentation of these tumours. To the best of our knowledge, this is the first case study of a neuroendocrine tumour presenting as paraneoplastic polyarthritis.